2003
DOI: 10.1080/0044929031000
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective vs. concurrent think-aloud protocols: Testing the usability of an online library catalogue

Abstract: Think-aloud protocols are a dominant method in usability testing. There is, however, only little empirical evidence on the actual validity of the method. This paper describes an experiment that compares concurrent and retrospective think-aloud protocols for a usability test of an online library catalogue. There were three points of comparison: usability problems detected, overall task performance, and participant experiences. Results show that concurrent and retrospective think-aloud protocols reveal comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
204
1
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(222 citation statements)
references
References 30 publications
(42 reference statements)
6
204
1
11
Order By: Relevance
“…Although CVP is the more commonly used protocol [8,12,19,20,22], in this study CVP only identified approximately half of the distinct problems, whereas RVP identified three quarters. This contradicts the results of previous studies conducted by van den Haak et al [25][26][27][28], that compared the two verbal protocols with sighted participants and found that they were comparable in terms of effectiveness. One possible explanation as to why the results are different lies in what van den Haak et al identify as a user problem.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Although CVP is the more commonly used protocol [8,12,19,20,22], in this study CVP only identified approximately half of the distinct problems, whereas RVP identified three quarters. This contradicts the results of previous studies conducted by van den Haak et al [25][26][27][28], that compared the two verbal protocols with sighted participants and found that they were comparable in terms of effectiveness. One possible explanation as to why the results are different lies in what van den Haak et al identify as a user problem.…”
Section: Discussioncontrasting
confidence: 57%
“…Comparing the two protocols in terms of whether they identify the same problems, we found that only 27 % of the distinct problems were identified by both protocols. Van den Haak et al [25][26][27][28]] also compared overlap between the two protocols in their studies. The overlap in most of the studies [25][26][27] was similar with the overlap reported in the study here, except for one study [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, reactivity might affect the working of the concurrent think-aloud method. The extent to which this happens has been and continues to be a much investigated topic (Russo et al, 1989;Ericsson and Simon, 1993;Van den Haak, De Jong & Schellens, 2003;Van den Haak, De Jong & Schellens, 2004;Alavi, 2005).…”
Section: Introductionmentioning
confidence: 99%